2014
DOI: 10.4102/sajip.v40i1.1227
|View full text |Cite
|
Sign up to set email alerts
|

A review of a decade’s scholarly publications (2004–2013) in the <i>South African Journal of Industrial Psychology</i>

Abstract: Orientation: Publishing methodologically sound, empirically based studies in reputable accredited scientific journals are essential in order to advance knowledge and evidence-based practice in the field of industrial and organisational psychology.Research purpose: The purpose of the research was to conduct a broad content analysis of the articles published in the South African Journal of Industrial Psychology (SAJIP) between 2004 and 2013. The study aimed to provide a descriptive overview of the most frequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 57 publications
(82 reference statements)
2
19
0
Order By: Relevance
“…With regard to the methods used, our data stayed true to literature, finding only common research methods (Grant and Booth, 2009;Maree, 2016) that varied in the degree to which they were employed. Quantitative research was found to be the most popular method, as indicated by literature (Breen and Darlaston-Jones, 2010;Counsell and Harlow, 2017) and previous studies in specific areas of psychology (see Coetzee and Van Zyl, 2014). Its long history as the first research method (Leech et al, 2007) in the field of psychology as well as researchers' current application of mathematical approaches in their studies (Toomela, 2010) might contribute to its popularity today.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the methods used, our data stayed true to literature, finding only common research methods (Grant and Booth, 2009;Maree, 2016) that varied in the degree to which they were employed. Quantitative research was found to be the most popular method, as indicated by literature (Breen and Darlaston-Jones, 2010;Counsell and Harlow, 2017) and previous studies in specific areas of psychology (see Coetzee and Van Zyl, 2014). Its long history as the first research method (Leech et al, 2007) in the field of psychology as well as researchers' current application of mathematical approaches in their studies (Toomela, 2010) might contribute to its popularity today.…”
Section: Discussionmentioning
confidence: 99%
“…Studies such as Lee et al ( 1999 ) as well as Bluhm et al ( 2011 ) review of qualitative methods has attempted to synthesis the use of research methods and indicated the growth of qualitative research in American and European journals. Research has also focused on the use of research methods in specific sub-disciplines of psychology, for example, in the field of Industrial and Organisational psychology Coetzee and Van Zyl ( 2014 ) found that South African publications tend to consist of cross-sectional quantitative research methods with underrepresented longitudinal studies. Qualitative studies were found to make up 21% of the articles published from 1995 to 2015 in a similar study by O'Neil and Koekemoer ( 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Third, to increase the trustworthiness of the thematic content analyses and the coding process, the data was independently analyzed by the co-ordinating author and one of the authors for each of the two separate sections (definition and model). Here open communication between the co-ordinating author and the three co-authors persisted throughout the analysis process (Coetzee and van Zyl, 2014). Disagreements in the coding process were discussed between the two coders until it was resolved.…”
Section: Selection Biasmentioning
confidence: 99%
“…For 45 years, the South African Journal of Industrial Psychology (SAJIP) has been at the vanguard of the struggle to advance industrial and organisational psychology (IOP) as a discipline within South Africa (Coetzee & Van Zyl, 2014Raubenheimer, 1994). Since its inception in 1974, under the editorships of Proffs.…”
Section: Introductionmentioning
confidence: 99%